Surgical outcome of posterior decompression, posterolateral fusion and stabilization by pedicle screw and rod in thoracolumbar tuberculosis (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
Spinal tuberculosis causes severe complications like neurological and spinal deformity which may lead to respiratory distress, costo-pelvic impingement, paraplegia and consequent reduction in the quality and longevity of life. The aim of the present treatment is to avoid the consequence of neural complications and gain near-normal spine. Mechanical factor causes pathological fracture or dislocation of an affected vertebral body. Surgical decompression ensues further instability. Reconstruction of spinal column by pedicle screw and rod provide stability and prevents secondary neural damage and deformity thereby helps in early mobilization. Prospective study was done to evaluate the results in 20 cases of spinal tuberculosis in thoracolumbar region associated with neurological deficit. We operated our cases (12 males and 8 females) by posterolateral decompression, fusion and stabilization by pedicle screw and rod along with antitubercular drug treatment. All patients were with neurological deficit, single level involvement and 10 to 30 degree of mild kyphosis. After surgery, kyphosis improved from 20.7 ± 5.5 degrees to 12.5 ± 3.9 degree. Bony fusion was in 65.0% cases. Neurological improvement and pain subsided in all the patients.